Clinical and echocardiographic characteristics of patients with pathology proven right-sided papillary fibroelastomas. (15th February 2022) - Ahmad, Ali; El-Am, Edward A.; Kurmann, Reto D.; Sorour, Ahmed A.; Bois, Melanie C.; Maleszewski, Joseph J.; Klarich, Kyle W.
Abstract: Background: Papillary fibroelastoma (PFE) are one of the most common primary cardiac neoplasms. They are most commonly found on cardiac valves especially on the left side of the heart and have been associated with an increased risk of embolization. To date, no large studies looked at the clinical significance of right-sided PFE (R-PFE). Therefore, we sought to better characterize patients with R-PFE and its clinical sequelae. Methods: We retrospectively identified patients with pathology-proven PFEs at a single center between January 1995 and December 2018 ( n  = 279). Patients with R-PFE were analyzed. Medical records and echocardiograms were reviewed for clinical and PFE characteristics. Results: Twenty-nine patients with R-PFE (mean age 70 ± 11 years; 62% women) were included in the analysis. PFEs were located on the right atrial (RA) wall in 31%, tricuspid valve in 34%, right ventricular (RV) wall in 7%, RV outflow tract in 4%, and pulmonary valve in 10% of patients. The remaining patients (14%) had multifocal PFEs. Around 38% of patients had cancer diagnosed before PFE diagnosis, and 34% had associated congenital heart disease. Seventeen (59%) patients had angina or dyspnea at the time of the presentation, and 3 (10%) had embolic symptoms. One patient with PFE located on the RA with associated patent foramen ovale had a stroke at time of presentation. Two patients, one with PFE on the RA wall and another patient with PFE at the tricuspid valve, had pulmonary embolism at the time of presentation. Median maximal length for PFE varied by location, ranging from a media of 8 mm to 16 mm. Of the 12 patients with follow up echocardiogram 1 year after PFE removal; 3/12 (25%) had documented PFE recurrence. Conclusion: R-PFE can be present in patients thromboembolic events when there is a right-to-left shunt. They can be a rare cause of pulmonary embolism, and at least in those that had follow-up echocardiograms, had a significant recurrence rate. Highlights: Right-sided PFE can have various serious clinical presentations. Right-sided PFE can be a cause of systemic emboli if associated with a shunt. Surgical removal provides an excellent management approach.